Precios y sociedad colonial (1700-1810): transformaciones en los mercados y ciclos económicos en Lima - Cosamalón Aguilar, Jesús A. (El Colegio de México, A.C., 2013)
This paper examines a topic rarely developed by Peruvian historiography: the study of colonial prices. Based on a hardly consulted source, the price edition published by Pablo Macera (1992), the author reviews the main price trends for European, regional and local goods, in order to establish the impact of Bourbon Reforms in Peru and to determine, through price series, the evolution of living conditions in the city. The essay also analyzes the integration between Limean and other markets, taking as reference the changes introduced by the Free Trade regulations.